Surface phytolith and pollen assemblages of a low-latitude subtropical region in Southwest China and their implications for vegetation and climate - Wang, Min; Yang, Qing; Yang, Wanshu; Shi, Lin; Zhang, Yu; Zhou, Zining; Zhang, Wuqi; Zheng, Hongbo (Frontiers in Plant Science, 2022)
Phytoliths, as a newly developing plant proxy, have broad application prospects in paleoclimate and paleoethnobotany. However, the shortage of studies regarding tropical-subtropical plants and topsoil phytoliths interferes with the research progress on primitive humanity's utilization of plant resources and paleoclimate in the region. This research focuses on the subtropical mountainous region with a monsoon climate of low latitudes in Southwest China to conduct phytolith morphology analysis of living plants and phytolith/pollen assemblages of topsoil to reveal the indicative significance of vegetation and climate. A total of 116 species from 51 families, including 73 species from 33 tree/shrub families, 36 species from 13 herb families and 7 species from 5 fern families, were collected for morphological characteristics analysis, as well as 19 topsoil specimens for phytolith and pollen assemblage analysis. The results suggest that phytoliths are mainly deposited in situ, with assemblages of topsoil corresponding well with plant types in the quadrat and being able to exhibit constructive species in small regions. In comparison, pollen assemblages of topsoil dominantly respond to regional vegetation due to their long-distance transportation and widespread presence, in addition to their characteristics that correspond to the vegetation in the quadrat. The topsoil phytolith assemblages are mainly based on the Elongate-Fan-Square/Rectangle-Broadleaf-types (including Globular echinate), and the vegetation types indicate the subtropical climate. In addition, phytolith assemblages of Poaceae are dominated by long saddle-fan-square/rectangle-elongate-point, reflecting warm and humid conditions. The pollen assemblages mainly consist of Pinus, Betula, Alnus, deciduous Quercus, Euphorbiaceae, Rhamnaceae and Polygonum, reflecting tropical-subtropical plant communities and indicating warm and humid conditions. Overall, phytolith and pollen assemblages have unique characteristics and are thus explicitly representative of the low-latitude subtropical monsoon climate.